Discovery of biphenyls bearing thiobarbiturate fragment by structure-based strategy as Mycobacterium tuberculosis protein tyrosine phosphatase B inhibitors - Cheng, Shihao; Wang, Qinglin; Chen, Xi; Chen, Jiahao; Wang, Bin; Chen, Dongni; Shen, Dong; Tian, Jinying; Ye, Fei; Lu, Yu; Huang, Haihong; Lu, Yongjun; et al. (Bioorganic & medicinal chemistry, 2022)
[Display omitted] Mycobacterium tuberculosis protein tyrosine phosphatase B (MptpB) is an important virulence factor that blocks the host immune response and facilitates M. tuberculosis growth in host cells. MptpB inhibitors are potential components of tuberculosis combination treatment. Herein, we present the development of new biphenyls MptpB inhibitors with greatly improved MptpB inhibition based on our reported thiobarbiturate lead 6 by rational design with the structure-based strategy. The eight biphenyls bearing thiobarbiturate fragment target compounds showed more potent MptpB inhibition (IC50: 1.18–14.13 μM) than the lead compound 6. Further molecular docking studies showed that compounds 13, 26, 27 and 28 had multiple interactions with active sites. Among them, compound 13 exhibited dose-dependent increased antituberculosis activity in mouse macrophages. The results displayed that the strategy of modification utilizing biphenyl scaffold was efficient. Our study identifies biphenyls bearing thiobarbiturate fragment as new MptpB inhibitors and verifies the therapeutic potential of antimycobacterial agent targeting MptpB.